Growth and Development of Toddlers in Rural and Urban Settings: A Correlational Study of Environmental Determinants - Verma, Ms. Neetu; Jaspher M, Mr. Justin; Dr. Kavichelvi K (Young Nurses Journal of Research, 2026)
Background of the study: Early childhood, particularly the toddler period (1–3 years), is a critical phase for physical growth and developmental maturation. Environmental determinants such as housing, sanitation, water supply, and pollution play an important role in shaping child health outcomes, yet comparative rural–urban evidence linking these factors with both growth and development remains limited in the Indian context. Objectives: To assess and compare the growth and developmental status of rural and urban toddlers and to examine the association between selected environmental variables and growth and developmental outcomes among toddlers residing in Lucknow, Uttar Pradesh. Materials & Methods: A quantitative, comparative descriptive survey design was adopted. Sixty toddlers aged 1–3 years (30 rural, 30 urban) were selected using convenience sampling. Growth was assessed using anthropometric measurements interpreted according to WHO growth standards, while developmental status was evaluated using a structured checklist adapted from the Denver Developmental Screening Test and ICDS guidelines. Environmental variables included housing condition, drinking water source, sanitation facilities, waste water disposal, and air pollution exposure. Data were analyzed using descriptive statistics, independent t-tests, and Spearman rank correlation analysis. Results: Normal growth was observed in 66.6% of rural toddlers and 80% of urban toddlers. Mean growth scores did not differ significantly between rural (5.53 ± 0.78) and urban toddlers (5.60 ± 0.89) (t = 0.308, p = 0.759). Similarly, developmental scores were comparable between rural (23.77 ± 4.46) and urban groups (24.77 ± 3.65) (t = 0.950, p = 0.346). Among rural toddlers, drinking water sources and sanitation facilities showed strong positive correlations with growth (rs = 0.700, p < 0.001), while housing condition demonstrated a significant association with developmental milestones (rs = 0.581, p < 0.01). In urban toddlers, air pollution was moderately associated with growth (rs = 0.530, p = 0.002), whereas drinking water, sanitation, and waste water disposal exhibited strong positive correlations with developmental outcomes (rs = 0.700, p < 0.001). Conclusion: Growth and developmental outcomes were broadly comparable between rural and urban toddlers; however, environmental determinants showed differential associations across settings. Safe drinking water, sanitation, and housing conditions emerged as key contributors to optimal growth and development. The findings emphasize the need for integrated, environment-focused child health interventions tailored to both rural and urban communities.